2016
DOI: 10.1159/000446812
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Profile and Antimicrobial Susceptibility of Bacteria Found in Inflammatory Hidradenitis Suppurativa Lesions

Abstract: Background: The role of bacterial colonization in hidradenitis suppurativa (HS) lesions is poorly understood. To date, data on the related microbial profile and especially on bacterial resistance rates are scarce. Methods: The results of bacterial cultures and susceptibility patterns of the isolated microorganisms obtained from deep portions of HS lesions from patients who underwent surgery at our HS Centre between 2010 and 2015 were retrospectively evaluated. Results: Analyses of 113 bacterial samples from 11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 37 publications
3
43
0
Order By: Relevance
“…Many dermatological patients suffer from different types of erosive skin lesions, e.g., follicular bacterial infections [22,23] or eczema [24]. Often, local antibiotics are used instead of considering antiseptic options for treatment, although according to expert opinion, the latter are more effective and do not pose a risk of resistance development [22]. This leads to the conclusion that further studies and observations must be undertaken to examine the potential of antiseptic treatment for these conditions.…”
Section: Evidence Regarding Wound Antisepticsmentioning
confidence: 99%
“…Many dermatological patients suffer from different types of erosive skin lesions, e.g., follicular bacterial infections [22,23] or eczema [24]. Often, local antibiotics are used instead of considering antiseptic options for treatment, although according to expert opinion, the latter are more effective and do not pose a risk of resistance development [22]. This leads to the conclusion that further studies and observations must be undertaken to examine the potential of antiseptic treatment for these conditions.…”
Section: Evidence Regarding Wound Antisepticsmentioning
confidence: 99%
“…Tregs are capable of suppressing an excessive or autoreactive immune‐mediated inflammatory response, especially the initiation, by preventing the activation and proliferation of T and B cells . In turn, in HS, host immune factors and an overactive immune system of the follicular epithelium can result in a dysregulated immune‐mediated inflammatory response with a possible important role in the initiation and progress of HS lesions . However, to the best of our knowledge only one previous study investigated the number of Tregs (CD4+ CD127 low FoxP3+) in blood samples of HS patients and found no difference between HS patients compared to healthy controls.…”
Section: Discussionmentioning
confidence: 93%
“…The latter ensues in painful nodules, abscess formation and in later stages, destruction of skin architecture, sinus tract formation and chronic inflammation. It has been suggested that host immune factors and an overactive immune system of the follicular epithelium play a major role in the pathogenesis of HS …”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, the authors did not specify the resistance pattern per bacterial species. From the 129 isolates, 42 were resistant to tetracycline (33%) …”
Section: Discussionmentioning
confidence: 99%
“…High antimicrobial resistance to clindamycin has been observed in bacterial isolates obtained from HS patients. An overall resistance rate of 71 of 129 isolates (71%) was found . In daily clinical practice, the combination therapy of rifampicin with clindamycin is often prescribed for the treatment of HS.…”
Section: Discussionmentioning
confidence: 99%